The association between blood pressure, renal function, and subclinical atherosclerosis in young and middle-aged non-hypertensive individuals: a mediation analysis - Lu, Wentao; Li, Wen; Zou, Zhuoqun; Yang, Qinyuan; Tian, Jianguang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aimed to investigate the interactions between blood pressure, renal function, and subclinical atherosclerosis in young and middle-aged individuals without hypertension.MethodsA total of 1,590 young and middle-aged individuals without hypertension were selected from the Shanghai Health and Medical Center database. Univariate and multivariate regression analyses were used to identify risk factors associated with subclinical atherosclerosis, and a mediation analysis using the bootstrap method was conducted to assess the mediating role of renal function between blood pressure and subclinical atherosclerosis.ResultsThe multivariate linear regression analysis identified significant correlations with age, gender, diastolic blood pressure (DBP), systolic blood pressure (SBP), glomerular filtration rate (GFR), history of cardiovascular disease (CVD), glycated hemoglobin (HbA1c), smoking history, and brachial-ankle pulse wave velocity (baPWV) (P < 0.05). The results indicated that GFR mediated the relationships of both systolic blood pressure (SBP) and diastolic blood pressure (DBP) with brachial-ankle pulse wave velocity (baPWV) (P < 0.05). The same is true among males after stratification by gender.ConclusionRenal function is independently associated with blood pressure and subclinical atherosclerosis after adjusting for confounders. Moreover, renal function mediates the relationship between blood pressure and subclinical atherosclerosis, also in males.